Joining of CVD-SiC coated and uncoated fibre reinforced ceramic matrix composites with pre-sintered Ti3SiC2 MAX phase using Spark Plasma Sintering. Issue 16 (December 2016) - Tatarko, Peter; Casalegno, Valentina; Hu, Chunfeng; Salvo, Milena; Ferraris, Monica; Reece, Michael J.
Abstract: CVD-SiC coated and uncoated ceramic matrix composites (Cf /SiC and SiCf /SiC) were joined to their counterparts with a pre-sintered Ti3 SiC2 foil using Spark Plasma Sintering. For the first time pre-sintered Ti3 SiC2 foil was used as a joining filler. The joining parameters were carefully selected to avoid the decomposition of Ti3 SiC2 and the reaction between the joining filler and the CVD-SiC coating, which would have deteriorated the oxidation protective function of the coating. Conformal behaviour of the Ti3 SiC2 foil during the diffusion joining and the infiltration of the joining filler into the surface cracks in the CVD β-SiC coating allowed the filler to be more integrated with the matrix material. While diffusion bonding occurred during joining of the coated composites, a combination of both solid-state reaction and diffusion bonding was observed for the uncoated Cf /SiC composites. This produced the lower shear strength (19.1 MPa) when compared to the diffusion bonded CVD-SiC coated Cf /SiC (31.1 MPa).